1997
DOI: 10.1021/jm9606599
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaromatic Analogs of 1-[2-(Diphenylmethoxy)ethyl]- and 1-[2-[Bis(4-fluorophenyl)methoxy]ethyl]-4-(3-phenylpropyl)piperazines (GBR 12935 and GBR 12909) as High-Affinity Dopamine Reuptake Inhibitors

Abstract: A new series of heteroaromatic GBR 12935 [1-[2-(diphenylmethoxy)ethyl]-4-(3-phenylpropyl)-piperazine] (I) and GBR 12909 [1-[2-[bis(4-fluorophenyl)methoxy]ethyl]-4-(3-phenylpropyl)piperazine] (2) analogs was synthesized and evaluated as dopamine transporter (DAT) ligands. Analogs 5-16, in which the benzene ring in the phenylpropyl side chain of the GBR molecule had been replaced with a thiophene, furan, or pyridine ring, exhibited high affinity and selectivity for the DAT vs serotonin transporter (SERT) and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…129 Although, self administration of GBR 12909 differed from cocaine in both rate and effective dose, suggesting differences in pharmacokinetics between these drugs. 129,130 Suppression of cocaine self-administration by GBR 12909 has been reported, 118 and in baboons, the behaviorally effective doses of GBR 12909 produce high occupancies of DAT as measured by PET imaging. 131 Behavioral evaluation of selected GBR 12909 analogs have been reported wherein some but not all demonstrated behavioral profiles that were similar to the parent drug.…”
Section: Behavioral Evaluation Of Gbr 12909 and Its Analogues As Compmentioning
confidence: 99%
See 2 more Smart Citations
“…129 Although, self administration of GBR 12909 differed from cocaine in both rate and effective dose, suggesting differences in pharmacokinetics between these drugs. 129,130 Suppression of cocaine self-administration by GBR 12909 has been reported, 118 and in baboons, the behaviorally effective doses of GBR 12909 produce high occupancies of DAT as measured by PET imaging. 131 Behavioral evaluation of selected GBR 12909 analogs have been reported wherein some but not all demonstrated behavioral profiles that were similar to the parent drug.…”
Section: Behavioral Evaluation Of Gbr 12909 and Its Analogues As Compmentioning
confidence: 99%
“…115 Additional modifications of the terminal phenyl ring of both GBR 12909 and 12935 by replacement with various heterocycles resulted in numerous novel and potent dopamine uptake inhibitors. 118,119 These heterocyclic analogues presumably possessed lower lipophilicities than the corresponding parent compounds, and thus may have more favorable bioavailability and pharmacokinetic profiles. On this line, a series of oxygenated analogues were prepared as well as their esterified pro-drugs for potential use as extended release agents.…”
Section: Gbr 12909 and Its Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the concentration of GBR 12909 (1 μM) used to inhibit DAT in striatum in the current study was based on numerous competition assays in studies of [ 3 H]DA uptake into striatal synaptosomes (e.g., Rothman et al, 1994), and this concentration is 1000-fold higher than the reported K i value for inhibition of [ 3 H]DA uptake into striatal synaptosomes (e.g., Matecka et al, 1997). Current follow-up experiments determined a K i value of 0.21 ± 0.01 μM for GBR 12909 inhibition of [ 3 H]5-HT uptake into hippocampal synaptosomes (data not shown), suggesting that the concentration of GBR 12909 used to inhibit DAT in striatal synaptosomes may have also affected 5-HT uptake via SERT.…”
Section: Discussionmentioning
confidence: 98%
“…The complete list of analogs, their experimental DAT and SERT binding affinity, as K i , and pK i (DAT/SERT) are shown in Tables 1A and 1B. 15,17,[46][47][48][49] The experimental pK i (DAT/SERT) in the table was calculated from the following equation: (1) Binding experiments were performed in the Rothman laboratory using identical protocols for all the analogs. 15, 17, 46-49 The K i value is nearly identical to the IC 50 value under these experimental conditions.…”
Section: Selection Of Analogsmentioning
confidence: 99%